Complex papillary hyperplasia of the endometrium: an uncommon case report with cytopathological features and diagnostic implications - Renjie Wang; Yinghong Wu; Zhihong Jia (Diagnostic Pathology)
Abstract Background Complex papillary hyperplasia of the endometrium (CPHE) is a rare benign lesion with overlapping features of malignancy, posing significant diagnostic challenges. This case highlights the importance of multidisciplinary evaluation to avoid misdiagnosis and overtreatment. Case presentation A 49-year-old premenopausal woman presented with irregular vaginal bleeding. Histopathological examination revealed multifocal lesions confined within and on the surface of endometrial polyps, exhibiting complex papillary structures with bland cytology. Immunohistochemistry showed strong ER/PR positivity and retained PTEN expression, while molecular analysis confirmed the absence of high-risk mutations (PTEN, PIK3CA, TP53, CTNNB1). Conclusions CPHE requires integration of histopathology, immunohistochemistry, and molecular diagnostics to distinguish it from malignancies. Conservative management is justified in molecularly confirmed cases.